2014
DOI: 10.1371/journal.pone.0115266
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Complicated Malaria in a Densely Forested Bastar Region of Chhattisgarh State (Central India)

Abstract: BackgroundA prospective study on severe and complicated malaria was undertaken in the tribal dominated area of Bastar division, Chhattisgarh (CG), Central India, with an objective to understand the clinical epidemiology of complicated malaria in patients attending at a referral hospital.MethodsBlood smears, collected from the general medicine and pediatric wards of a government tertiary health care facility located in Jagdalpur, CG, were microscopically examined for malaria parasite from July 2010 to December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 27 publications
(46 reference statements)
0
18
0
Order By: Relevance
“…In the present investigation, we determined the IgG antibody response against synthetic peptides representing the conserved region of B cell & T cell of msp1, csp and B cell of msp2, glurp among patients infected with P . falciparum in Central India, where malaria is endemic [ 51 ]. In this study, majority of the plasma samples reacted against the B cell epitope of pfmsp1 and pfcsp despite its short amino acid sequence.…”
Section: Discussionmentioning
confidence: 99%
“…In the present investigation, we determined the IgG antibody response against synthetic peptides representing the conserved region of B cell & T cell of msp1, csp and B cell of msp2, glurp among patients infected with P . falciparum in Central India, where malaria is endemic [ 51 ]. In this study, majority of the plasma samples reacted against the B cell epitope of pfmsp1 and pfcsp despite its short amino acid sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, treatment seeking behavior, occupational activities and socio-cultural barriers promote male to reach the higher health centers [12], [13] . Vidhan Jain et al observed male predominance in hospitalization pattern of malaria [1] . Pathak et al also had the similar opinion as Vidhan Jain [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Majority of hospitalization of malaria due Falciparum is the main and most important finding of the study. In one of the study which was carried out by Vidhan Jain et al in highly tribal region of India namely Bastar District of Chhattisgarh in which tribal population is mainly involved in agriculture and forest, observed 9% slide positivity rate with almost 50% incidence of plasmodium falciparum [1] . They found 5 years as median age of malaria and associated morbidity in children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations